Polyunsaturated fatty acid biosynthesis is involved in phenylephrine-mediated calcium release in vascular smooth muscle cells. (October 2015) - Irvine, Nicola A.; Lillycrop, Karen A.; Fielding, Barbara; Torrens, Christopher; Hanson, Mark A.; Burdge, Graham C.
Abstract: Stimulation of vascular smooth muscle (VSM) α1 -adrenoceptors induces myosin phosphorylation and vasoconstriction via mobilisation of intracellular calcium and production of specific eicosanoids. Polyunsaturated fatty acid (PUFA) biosynthesis in VSM cells is involved, although the precise mechanism is not known. To address this, we characterised PUFA biosynthesis in VSM cells and determined its role in intracellular calcium release and eicosanoid production. Murine VSM cells converted 18:2n-6 to longer chain PUFA including 22:5n-6. Δ6 (D6d) and Δ5 (D5d) desaturase, and elongase (Elovl) 5 were expressed. Elovl2 was not detected in human, mouse or rat VSM cells, or in rat or mouse aortae, but tit was not associated with hypermethylation of its promoter. D6d or D5d inhibition reduced 18:3n-6 and 20:4n-6 synthesis, respectively, and induced concentration-related decrease in phenylephrine-mediated calcium release, and in PGE2 and PGF2α secretion. Together these findings suggest that PUFA biosynthesis in VSM cells is involved in calcium release associated with vasoconstriction.